Complications in gastrointestinal endoscopy: a summary at the first international symposium in Hannover 2009 - Meier, P. N. (Endoscopy, 2011)
Following the recent success of the Second International Symposium on Complications in Gastrointestinal Endoscopy (17–18 June 2011, Hannover, Germany), it would be worth reminding ourselves of the key points and highlights of the first symposium held in Hannover in June 2009. The congress, which is endorsed by the American Society for Gastrointestinal Endoscopy (ASGE) under the patronage of the European Society for Gastrointestinal Endoscopy (ESGE), is designed to bring together endoscopists and support staff to present and discuss the diagnosis, treatment, and prevention of complications associated with gastrointestinal endoscopy, including effective communication strategies and management in particular patient groups. This current report is a brief summary of topics discussed at the inaugural symposium in 2009.